Effects of dopamine D2 receptor gene polymorphisms on smoking cessation: Abstinence and withdrawal symptoms - Munafo, MR; Johnstone, E (2007)
An increasing number of studies have investigated the role of genetic factors in smoking cessation, and in response to smoking cessation pharmacotherapy. Robinson and colleagues report data on the effects of the dopamine D2 receptor gene Taq1B polymorphism on smoking cessation and withdrawal. While the results add to the growing literature on smoking cessation pharmacogenetics, they also illustrate that minor differences in phenotype definition may influence the results of pharmacogenetic analyses. Existing studies also lack direct comparability, which makes it difficult to judge evidence for replication. Several future directions for smoking cessation pharmacogenetics research are discussed. © 2007 Future Medicine Ltd.